Hormonal induction of spermiation in a Eurasian bufonid (Epidalea calamita) - Lucía Arregui; Sergio Diaz-Diaz; Elia Alonso-López; Andrew J. Kouba (BMC, 2019)
Abstract Background Amphibian diversity is declining at an alarming rate due to habitat loss, invasive species, climate change and diseases. Captive assurance colonies have been established for some species at risk; however, many species do not breed well in captivity and the development of assisted reproductive technologies (ART) is critical to help sustain genetic diversity. To date, the majority of the work has been accomplished in species from the American continent and Australia, and there is a need to address similar breeding challenges in Eurasian and African species of amphibians. Methods The aim of this study was to develop a hormone protocol for stimulation of spermiation in Epidalea calamita as a model for Eurasian bufonids. Hence, the effect on sperm production and quality of three doses of chorionic gonadotropin hormone (5, 10 and 15 IU hCG/g) over time (1 to 24 h) was evaluated. In addition, cold storage (at 5 °C) of sperm for 24 and 48 h and three frequencies for hormonal treatment (weekly, biweekly and monthly) were examined. Results Hormone concentrations of 10 or 15 IU of hCG induced spermiation in 100% of males and produced sperm of comparable quality, while 5 IU hCG stimulated spermiation in only 40% of males. Total motility peaked between 1 to 4 h post-treatment with 10 IU hCG, whereas treatment with 15 IU hCG peaked between 2 to 6 h. After 24 h of cold storage total motility dropped by 20% and forward motility dropped by 10% for both the 10 and 15 IU treatments. Weekly hormone administration resulted in higher variation between trials in all motility parameters and a lower overall Total Motility and Forward Movement. Furthermore, the effect of exogenous hormone treatment overlapped between the last two trials in the weekly frequency. Sperm concentration was higher in the first trial for all frequencies but showed no differences among other trials. Conclusions Overall, these results show that hormone concentration, time after treatment, frequency of hormone treatment and cold storage should be borne in mind when developing a hormone stimulation protocol for Eurasian amphibian species.